2016
DOI: 10.1128/jvi.00502-16
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus E2 Protein: Linking Replication, Transcription, and RNA Processing

Abstract: The human papillomavirus (HPV) life cycle is tightly linked to differentiation of the infected epithelium. This means that viral proteins must exert control over epithelial gene expression in order to optimize viral production. The HPV E2 protein controls replication, transcription, and viral genome partitioning during the viral infectious life cycle. It consists of a nucleic acid-binding domain and a protein-protein interaction domain separated by a flexible serine and arginine-rich hinge region. Over the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…In addition to cellular RNA binding proteins, HPV16 E2 contributes directly to the control of HPV16 RNA processing by interfering with HPV16 RNA polyadenylation ( 14 ). HPV16 E2 has also been shown to affect HPV16 RNA processing indirectly by activating expression of splicing factors ( 15 ), possibly a result of E2 binding to cellular DNA ( 16 ). Cellular factors such as CTCF may also control both transcription and processing of HPV mRNAs ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cellular RNA binding proteins, HPV16 E2 contributes directly to the control of HPV16 RNA processing by interfering with HPV16 RNA polyadenylation ( 14 ). HPV16 E2 has also been shown to affect HPV16 RNA processing indirectly by activating expression of splicing factors ( 15 ), possibly a result of E2 binding to cellular DNA ( 16 ). Cellular factors such as CTCF may also control both transcription and processing of HPV mRNAs ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular factors such as CTCF may also control both transcription and processing of HPV mRNAs ( 17 ). Much of HPV16 gene regulation occurs at the level of RNA processing ( 8 , 15 , 18 ) and HPVs produce a large number of alternatively spliced and polyadenylated mRNAs ( 9 ). A number of cis acting RNA elements controlling HPV16 and HPV18 splices sites and polyA signals have been identified and characterized ( 8 ), and a review of all identified HPV RNA binding proteins has recently been published ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…E2 is a protein of about 365 amino acids (HPV genotype 16; its length varies among genotypes) whose expression gradually increases from the mid- to upper layers of infected lesions. This pattern of expression reflects the key role of E2 in the coordination of late events of viral replication through its influence on transcription, viral genome replication and partitioning in dividing cells, and RNA processing (reviewed by Graham, 2016 ).…”
Section: Hpvmentioning
confidence: 90%
“…The present study has focused on this type of HPV. The HPV E2 protein controls replication, transcription and viral genome partitioning during the viral infectious life cycle ( 16 ). The HPV E2 protein is a key transcriptional regulator of the E6 and E7 genes ( 17 ).…”
Section: Introductionmentioning
confidence: 99%